USE OF GENE XPERT MTB/RIF ASSAY FOR DETECTING MYCOBACTERIUM TUBERCULOSIS AND RIFAMPICIN RESISTANCE - ULLAH, U; MEHMOOD, M; IRFAN, M; RAZZQA, MA; ATIF, M (Biological and Clinical Sciences Research Journal, 2022)
The current study was designed to assess the specificity and sensitivity of MTB/RIF assay for early detection of Mycobacterium tuberculosis and RIF resistance in smear-positive and smear-negative pulmonary and extrapulmonary samples. This retrospective study was conducted in Bakhtawar Amin Trust Hospital Multan from July 2021 to July 2022. Total 240 pulmonary samples (gastric fluid specimens, post-bronchoscopic sputum, bronchoscopic aspirate, bronchoalveolar lavage and sputum) and 170 extra-pulmonary samples (urine specimens, skin biopsy, pericardial fluid, cerebrospinal fluid, ascitic fluid, disc material, lymph node biopsy and pleural fluid) were collected. After culture growth and identification of species, drug susceptibility testing (DST) was done. All samples underwent Xpert MTB/RIF assay. A total of 240 pulmonary and 170 extra-pulmonary samples from 410 patients were collected. The mean age of the patients was 46.5 ± 10 years. Of 410 subjects, 100 had TB, and 310 had no evidence of TB. Of 100 TB patients, the specificity of the MTB/RIF assay was 100 % (100), sensitivity was 69% (69), PPV was 100% (100), and NPV was 91% (91). According to the MTB/RIF assay, 79 samples were RIF-susceptible, and 1 was RIFresistant; DST confirmed the results. MTB/RIF assay is a valuable tool for detecting Mycobacterium tuberculosis and rifampicin resistance. It is not technique sensitive and provides results in less than three hours.